PENGARUH DEBT TO EQUITY RATIO, EARNING PER SHARE DAN NET PROFIT MARGIN TERHADAP RETURN SAHAM PADA INDUSTRI FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 20112016 - Lastari, Adria Wuri (JUMANJI (JURNAL MANAJEMEN JAMBI), 2018)
The purpose of this study was to analyze the effect of Debt to Equity Ratio, Earning PerShare and Net Profit Margin Against Return of Food and Beverages Industry Stock Listed onIndonesia Stock Exchange Period 2011-2016. Stock return is the result of investment activity.The problem of this research is whether there is any influence of Debt to Equity Ratio (DER),Earning Per Share (EPS) and Net Profit Margin (NPM) partially or simultaneously to stockreturn.The population of this research is Food and Beverages company listed in IndonesiaStock Exchange. The sample in this research is Food and Beverages Industry Companywhich consistently listed on BEI 2011 until 2016 that is 9 companies. The data collected wereanalyzed by using multiple linear regression analysis with partial test hypothesis test (t test)and simultaneous test (Test F). Hypothesis test using t statistic to test the partial variableinfluence and F-statistic test to test the variables jointly to stock return with level ofsignificance 5%. In addition, a classical assumption test that includes normality test,multicollinearity test, heteroscedasticity test and autocorrelation test. The result of regressionanalysis of data shows the following equation Y = 5,663 - 0,173 X1 + 0,23 X2 + 0,32 X3.Based on multiple regression analysis, it shows partially that DER, EPS and NPM havenegative but not significant influence. And simultaneously (simultaneously) all the variablesalso have no significant effect. The magnitude of the effect of DER, EPS and NPM on Returnon Food and Beverages sector in Indonesia Stock Exchange period 2011-2016 is 3.10%while the rest of 96.0% is determined by other factors not specified in this research. Theconclusion of this research is that there is no partial and simultaneous influence offundamental factor that is ratio of DER, EPS and NPM to stock return. For investors it isadvisable to consider the external factors of the company in addition to fundamental factorssuch as economic conditions both nationally and globally, political and legal conditions forinvestment decisions in a company more appropriate.